Novel Role for Interleukin-17 in Enhancing Type 1 Helper T Cell Immunity in the Female Genital Tract following Mucosal Herpes Simplex Virus 2 Vaccination - Bagri, Puja; Anipindi, Varun C; Nguyen, Philip V; Vitali, Danielle; Stämpfli, Martin R; Kaushic, Charu (Journal of virology, 2017)
It is well established that interferon gamma (IFN-γ) production by CD4 T cells is critical for antiviral immunity against herpes simplex virus 2 (HSV-2) genital infection. However, the role of interleukin-17A (IL-17A) production by CD4 T cells in HSV-2 antiviral immunity is yet to be elucidated. Here we demonstrate that IL-17A plays an important role in enhancing antiviral T helper type 1 (T 1) responses in the female genital tract (FGT) and is essential for effective protection conferred by HSV-2 vaccination. While IL-17A did not play a critical role during primary genital HSV-2 infection, seen by lack of differences in susceptibility between IL-17A-deficient ( ) and wild-type (WT) C57BL/6 mice, it was critical for mediating antiviral responses after challenge/reexposure. Compared to WT mice, mice (i) infected intravaginally and reexposed or (ii) vaccinated intranasally and challenged intravaginally demonstrated poor outcomes. Following intravaginal HSV-2 reexposure or challenge, vaccinated mice had significantly higher mortality, greater disease severity, higher viral shedding, and higher levels of proinflammatory cytokines and chemokines in vaginal secretions. Furthermore, mice had impaired T 1 cell responses after challenge/reexposure, with significantly lower proportions of vaginal IFN-γ CD4 T cells. The impaired T 1 cell responses in mice coincided with smaller populations of IFN-γ CD4 tissue resident memory T (T ) cells in the genital tract postimmunization. Taken together, these findings describe a novel role for IL-17A in regulating antiviral IFN-γ T 1 cell immunity in the vaginal tract. This strategy could be exploited to enhance antiviral immunity following HSV-2 vaccination. T helper type 1 (T 1) immunity, specifically interferon gamma (IFN-γ) production by CD4 T cells, is critical for protection against genital herpesvirus (HSV-2) infection, and enhancing this response can potentially help improve disease outcomes. Our study demonstrated that interleukin-17A (IL-17A) plays an essential role in enhancing antiviral T 1 responses in the female genital tract (FGT). We found that in the absence of IL-17A, preexposed and vaccinated mice showed poor disease outcomes and were unable to overcome HSV-2 reexposure/challenge. IL-17A-deficient mice ( ) had smaller populations of IFN-γ CD4 tissue resident memory T (T ) cells in the genital tract postimmunization than did wild-type (WT) mice, which coincided with attenuated T 1 responses postchallenge. This has important implications for developing effective vaccines against HSV-2, as we propose that strategies inducing IL-17A in the genital tract may promote more effective T 1 cell immunity and better overall protection.